Bovine Coronavirus Infects the Respiratory Tract of Cattle Challenged Intranasally - Soules, Katelyn R.; Rahe, Michael C.; Purtle, Lisa; Moeckly, Craig; Stark, Paul; Samson, Clay; Knittel, Jeffrey P. (Frontiers in Veterinary Science, 2022)
Bovine Coronavirus (BCoV) is a member of a family of viruses associated with both enteric and respiratory diseases in a wide range of hosts. BCoV has been well-established as a causative agent of diarrhea in cattle, however, its role as a respiratory pathogen is controversial. In this study, fifteen calves were challenged intranasally with virulent BCoV in order to observe the clinical manifestation of the BCoV infection for up to eight days after initial challenge, looking specifically for indication of symptoms, pathology, and presence of viral infection in the respiratory tract, as compared to six unchallenged control calves. Throughout the study, clinical signs of disease were recorded and nasal swabs were collected daily. Additionally, bronchoalveolar lavage (BAL) was performed at four days post-challenge, and blood and tissue samples were collected from calves at four, six, or eight days post-challenge to be tested for the presence of BCoV and disease pathology. The data collected support that this BCoV challenge resulted in respiratory infections as evidenced by the isolation of BCoV in BAL fluids and positive qPCR, immunohistochemistry (IHC), and histopathologic lesions in the upper and lower respiratory tissues. This study can thus be added to a growing body of data supporting that BCoV is a respiratory pathogen and contributor to respiratory disease in cattle.